2017
DOI: 10.1152/ajpcell.00048.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between increased intracellular zinc (Zn2+) and accumulation of reactive oxygen species in chemical ischemia

Abstract: Both zinc (Zn) and reactive oxygen species (ROS) have been shown to accumulate during hypoxic-ischemic stress and play important roles in pathological processes. To understand the cross talk between the two of them, here we studied Zn and ROS accumulation by employing fluorescent probes in HeLa cells to further the understanding of the cause and effect relationship of these two important cellular signaling systems during chemical-ischemia, stimulated by oxygen and glucose deprivation (OGD). We observed two Zn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 77 publications
(121 reference statements)
2
31
0
Order By: Relevance
“…Further examination revealed that an OGD-induced increase in neuronal [Zn 2+ ] i preceded mitochondrial depolarization, Ca 2+ deregulation and membrane failure, with Zn 2+ likely entering mitochondria and contributing to loss of mitochondrial membrane potential (Medvedeva et al, 2009). This meshed with earlier demonstration that elevated intracellular Zn 2+ , like Ca 2+ , can enter and damage mitochondria, leading to their swelling, loss of membrane potential and, at high levels of Zn 2+ , increased ROS generation (Sensi et al, 2003;Clausen et al, 2013), the last likely a consequence of disturbances in mitochondrial electron transport as well as Zn 2+ induction of p47 PHOX and increased NOX activity (Noh and Koh, 2000;Slepchenko et al, 2017). Downstream ROS/RNS-induced release of Zn 2+ from intracellular stores (Berendji et al, 1997;Cuajungco and Lees, 1998;Aizenman et al, 2000) thus drives further oxidative stress.…”
Section: Zincsupporting
confidence: 70%
“…Further examination revealed that an OGD-induced increase in neuronal [Zn 2+ ] i preceded mitochondrial depolarization, Ca 2+ deregulation and membrane failure, with Zn 2+ likely entering mitochondria and contributing to loss of mitochondrial membrane potential (Medvedeva et al, 2009). This meshed with earlier demonstration that elevated intracellular Zn 2+ , like Ca 2+ , can enter and damage mitochondria, leading to their swelling, loss of membrane potential and, at high levels of Zn 2+ , increased ROS generation (Sensi et al, 2003;Clausen et al, 2013), the last likely a consequence of disturbances in mitochondrial electron transport as well as Zn 2+ induction of p47 PHOX and increased NOX activity (Noh and Koh, 2000;Slepchenko et al, 2017). Downstream ROS/RNS-induced release of Zn 2+ from intracellular stores (Berendji et al, 1997;Cuajungco and Lees, 1998;Aizenman et al, 2000) thus drives further oxidative stress.…”
Section: Zincsupporting
confidence: 70%
“…The aberrant homeostasis of transition metal ions, e.g., Fe 2+ /Fe 3+ , Zn 2+ , and Ca 2+ , plays important roles in the pathogenesis of various diseases. For instance, a recent study has highlighted the interaction of Zn 2+ homeostasis and ROS signaling suggesting their interdependence 49 . Mitochondria contain dynamic pools of these metal ions that are incorporated into corresponding metalloproteins 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that zinc deficiency increases oxidative stress [ 22 , 116 , 117 ]. It is well accepted that oxidative damage is a major cause of tissue injury and redox regulation plays a prominent role in wound repair [ 118 , 119 , 120 ].…”
Section: Zinc Is An Antioxidant Micronutrientmentioning
confidence: 99%